2013
DOI: 10.1002/malq.201200015
|View full text |Cite
|
Sign up to set email alerts
|

A consistency proof for some restrictions of Tait's reflection principles

Abstract: In [5] Tait identifies a set of reflection principles which he calls Γ(2) n -reflection principles which Peter Koellner has shown to be consistent relative to κ(ω), the first ω-Erdös cardinal, in [2]. Tait also goes on in the same work to define a set of reflection principles which he calls Γ (m) n -reflection principles; however Koellner has shown that these are inconsistent when m > 2 in [3], but identifies restricted versions of them which he proves consistent relative to κ(ω). In this paper we introduce a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…If we modify the reflection principle so as only to apply to formulas in which unbounded existential quantifiers for first-order variables do not appear within the scope of a higher-order quantifier (but existential quantifiers bound by a firstorder variable are allowed), then the resulting reflection principle becomes consistent relative to an ω-Erdős cardinal. In fact a level V κ satisfies this form of reflection if and only if κ is ω-refelctive in the sense defined in [6], and when this is so then V κ satisfies Γ…”
Section: Intrinsic Justifications For Small Large Cardinalsmentioning
confidence: 99%
See 1 more Smart Citation
“…If we modify the reflection principle so as only to apply to formulas in which unbounded existential quantifiers for first-order variables do not appear within the scope of a higher-order quantifier (but existential quantifiers bound by a firstorder variable are allowed), then the resulting reflection principle becomes consistent relative to an ω-Erdős cardinal. In fact a level V κ satisfies this form of reflection if and only if κ is ω-refelctive in the sense defined in [6], and when this is so then V κ satisfies Γ…”
Section: Intrinsic Justifications For Small Large Cardinalsmentioning
confidence: 99%
“…In Section 2 I will describe the ideas about intrinsic justification which originally led me to think that the existence of remarkable cardinals was intrinsically justified. Then in Section 3 I will analyze the relationship between the reflection principles of [6] and [7] with those of [1], [2] and [14], and consider the philosophical question whether there can be any principled grounds for accepting the former but not the latter. I will also discuss how a natural extension of the reflection principle put forward by Roberts is equivalent to the existence of a supercompact cardinal.…”
Section: Introductionmentioning
confidence: 99%
“…Formulating a notion of an α-reflective cardinal for ordinals α > 0 and seeking to motivate this along lines inspired by remarks in the work of Tait, I showed in [7] that if κ is ω-reflective then V κ satisfies RP m,n for all m, n with some restrictions on φ slightly more restrictive than Tait's ones. And I showed that it is consistent relative to an ω-Erdős cardinal that there is a proper class of α-reflective cardinals for each α > 0.…”
Section: Introductionmentioning
confidence: 99%
“…But Koellner [16], building on some results of Tait, shows that no V κ can reflect the class of formulas of the form ∀X ∃Yϕ(X, Y, Z), where X is of third-order, Y is of any finite order, Z is of fourth order, and ϕ has only first-order quantifiers and its only negated atomic subformulas are either of first order or of the form x ∈ X , where x is of first order and X is of second order. Other kinds of restrictions on the class of sentences to be reflected are possible (see [26] for the consistency of some forms of reflection slightly stronger than Tait's Γ (2) ), but Koellner [16] convincingly shows that the existence of a cardinal κ such that V κ reflects any reasonable expansion of the class of sentences Γ (2) , with parameters of order greater than 2, either follows from the existence of κ( ) or is outright inconsistent. These results seem to put an end to the program of providing an intrinsic 3 justification of large-cardinal axioms, even for axioms as strong as the existence of κ( ), by showing that their existence follows from strong higherorder reflection properties holding at some V κ .…”
mentioning
confidence: 99%